P255 The Effects of Hypoxia on Neutrophil Degranulation. (19th November 2012) - Hoenderdos, K; Porter, L; Alam, S; Govern, N Mc; Fiddler, C; Skepper, J; Chilvers, ER; Condliffe, AM
Abstract : Tissues such as the skin and intestinal epithelium experience physiological hypoxia whereas pathological hypoxia occurs at inflammatory sites. Neutrophils are recruited to infective/inflamed areas and are thus required to operate under low oxygen tensions. We have shown previously that hypoxia delays neutrophil apoptosis (JEM 2005; 201:105) and impairs bacterial killing (J Immunol 2011; 186:453) and have now studied the effect of hypoxia on the release of histotoxic neutrophil proteases. Neutrophils isolated from healthy volunteers were subjected to normoxia or hypoxia (3 kPa). Superoxide anion release was measured by the reduction of cytochrome. C Elastase release was quantified by the cleavage of labelled elastin. Hypoxic incubation for 4 hours resulted in a 3- fold reduction in superoxide anion release from cells stimulated with GM-CSF and fMLP. In contrast, elastase release from the azurophilic granules was augmented almost 3-fold under hypoxia. The release of MMP-9 and lactoferrin was similarly up-regulated, suggesting a more generalised increase in degranulation under hypoxia. In addition to this electron microscopy showed that hypoxia induced a more activated phenotype (e.g. increased membrane ruffling and cell spreading). We show that hypoxia can induce a more destructive neutrophil phenotype, with enhanced degranulation and release of potentially histotoxic proteases, impaired bacterial killing, and delayed apoptosis. These data suggest that hypoxia aversively affects neutrophil function and may augment neutrophil mediated tissue destruction.